2.3 Effect dimercaptopropanol (BAL) in polycythemia by cobalt - Guzmán Barrón, Alberto (1949)
During the Second World War there have been interesting research on the action of 2,3 dimercapto-propanol in poisoning by various substances, both in animals and men, and of particular interest to those of therapeutic use. As work arrived to our hands we have not we found studios with respect to cobalt, which in high doses exerts a toxic action and in small doses can cause polycythemia in various animals, the mechanism until today still remains unclear, we decided to study the effect that the Bal might exist in relation to cobalt. The first results are found regarding this communication.